PENGARUH CITRA MEREK DAN KUALITAS PRODUK TERHADAP KEPUASAN KONSUMEN SEPATU OLAHRAGA MERK NIKE (STUDI KASUS KOMUNITAS BASKET KOTA PALEMBANG) - Warni, Zubaidah; Mianto Pane, Sugeng; Sri Gunarti, Triana; A Rinandi, Alditya (TECHNOBIZ : International Journal of Business, 2026)
Sport is a form of physical activity that is usually competitive in nature with the aim of improving a person's physical abilities and skills while providing entertainment for players and spectators. One type of sport that is popular with people is basketball. The majority of world athletes use the Nike sports brand, whether for their shoes or clothing. Moreover, several athletes from the world of basketball are Brand Ambassadors for this brand. The Nike brand itself is currently a sponsor of the world basketball competition, namely the NBA. This research aims to find out whether there is an influence of brand image and kualitas produk on consumer satisfaction for Nike sports shoe users. The sample in the research are 100 basketball activists in Palembang. The research method is presented quantitatively, based on questionnaires distributed to respondents. Next, the data is processed using the SPSS 26 program. The final aim of this research is to find out whether there is an influence of brand image and kualitas produk on consumer satisfaction, either partially or simultaneously.